Pengalaman meditasi Ānāpānasati dalam meningkatkan fungsi kognitif dan mengurangi kecemasan sosial pada siswa sekolah minggu Buddhis (Vihara Theravada Buddha Sasana) - Candra Mukti (Advances In Education Journal, 2026)
This study has several objectives to analyze the effectiveness of students' meditation practices using the Ānāpānasati meditation object to improve cognitive function and reduce social anxiety in Buddhist Sunday School students. This study uses a phenomenological approach involving three participants aged 13–16 years who regularly meditate. Data were collected through in-depth interviews, participatory observation, and student self-reflection. The results of the study indicate that breathing meditation has several positive effects on improving concentration in learning, controlling emotions, and reducing social anxiety. The results of this approach indicate that the practice of Ānāpānasati meditation can be effectively integrated into Buddhist character education, which can lead to progress in the students' inner balance and self-awareness.